A Combination of Two Receptor Tyrosine Kinase Inhibitors, Canertinib and PHA665752 Compromises Ovarian Cancer Cell Growth in 3D Cell Models. Issue 2 (December 2016) - Hassan, Wafaa; Chitcholtan, Kenny; Sykes, Peter; Garrill, Ashley
Abstract Introduction Advanced ovarian cancer is often a fatal disease as chemotherapeutic drugs have limited effectiveness. Better targeted therapy is needed to improve the survival and quality of life for these women. Receptor tyrosine kinases including EGFR, Her-2 and c-Met are associated with a poor prognosis in ovarian cancer. Therefore, the co-activation of these receptors may be crucial for growth promoting activity. In this study, we explored the effect of combining two small molecule inhibitors that target the EGFR/Her-2 and c-Met receptor tyrosine kinases in two ovarian cancer cell lines. The aim of this study was to investigate the combined inhibition activity of a dual EGFR/Her-2 inhibitor (canertinib) and a c-Met inhibitor (PHA665752) in ovarian cancer cell lines in 3D cell aggregates. Methods OVCAR-5 and SKOV-3 ovarian cancer cell lines were cultured on a non-adherent surface to produce 3D cell clusters and aggregates. Cells were exposed to canertinib and PHA665752, both individually and in combination, for 48 h. The effect on growth, metabolism and the expression/phosphorylation of selective signaling proteins associated with EGFR, Her-2 and c-Met were investigated. Results The single drug treatments significantly decreased cell growth and altered the expression of signaling proteins in OVCAR-5 and SKOV-3 cell lines. The combination treatment showed greater reduction of cell numbers for both cell lines. Total expression and phosphorylation of signaling proteins were further reduced in the combination drug treatments, compared to the single inhibitor treatments. Conclusion Our findings suggest that the concurrent targeting of more than one receptor tyrosine kinase may be useful in developing more effective targeted drug regimens for patients, who have EGFR, Her-2 and c-Met positive ovarian cancer cells.